Pengaruh Bisnis E-Commerce, Teknologi Informasi, dan Kompetensi Auditor terhadap Kebutuhan Jasa Audit E-Commerce : Studi Kasus pada Kantor Akuntan Publik Kota Surabaya - Puspitasari, Mia; Tannar, Oryza (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to find the impact of e-commerce business, information technology, and auditor competence on the need for e-commerce audit services provided by Public Accounting Firms (KAP) registered with the Indonesian Institute of Certified Public Accountants (IAPI) in Surabaya. Using a quantitative approach, this study involved a sample of 52 auditors selected through basic random sampling methodology and the Slovin formula. Questionnaire distribution was the main method for data collection in this study. Data analysis relied on Partial Least Square (PLS) software. The results of this study reveal that the demand for e-commerce audit services continues to increase, influenced by the growth of e-commerce businesses, and the level of auditor competence, while advances in information technology have no effect.